Module Development Traditional Bugis Ethnic Food in Johor - Abdul Rahman, Abdul Wafi; Mat Naim, Afiqah; Md Sahak, Adibah Aishah; Ismail, Nurul Ashikin; Hashim, Noliza (Research and Innovation in Technical and Vocational Education and Training, 2024)
Modules are one of the materials that can be used to help make the teaching and learning process easier. This study was conducted to address the shortage of modular reference sources. The objective of the study was to design the Traditional Bugis Ethnic Food Module in Johor and to evaluate the suitability of the Traditional Bugis Ethnic Food Module in Johor in terms of content, format, clarity, and design of the module used. To conduct this study, quantitative methodologies were used. To assess the viability of the module being produced, a set of questionnaires with 20 items and expert verification forms were given to five professionals, who are academics from Tun Hussein Onn University in Malaysia’s Faculty of Technical and Vocational Education. Feedback from the results of the questionnaire and expert verification forms were then presented in a table format to facilitate reading. The study found that the development of the Traditional Bugis Ethnic Food module in Johor received positive feedback from the experts. In conclusion, from the findings of the study, the modules developed correspond to the content, module format, module clarity, and predefined module design.